Analisis Revitalisasi Desa Wisata dengan Mengoptimalkan Ekonomi Kreatif Melalui UMKM Berbasis Digital Pada Desa Sigapiton - Eko Deswin Miechaels Siringoringo; Muhammad Yunus (Owner : Riset dan Jurnal Akuntansi, 2022)
Sigapiton Village is one of the villages in North Toba Regency which until now has not applied technology in economic activities, especially people's businesses, both UMKM, IKM, Cooperatives, and others.. The potential that is owned is not managed properly due to limited Human Resources so that the use of technology is also limited. The purpose of this study is to analyze the revitalization of tourist villages by optimizing the creative economy through technology-based SMEs. The stages of the research process start from the initial planning, namely making a written plan or plan by determining the date of implementation and the person in charge. After the research plan is summarized, the researcher immediately conducts an initial survey to obtain basic information about the topic to be studied. Data collection techniques were carried out by interview and observation. The analytical technique used is the Grounded Theory method, which is a qualitative analysis model using systematic procedures to develop scientific theories based on existing phenomena. The results of this study are digital-based SMEs are one of the most appropriate solutions to be applied to increase the productivity of business actors in Sigapiton Village, especially in terms of increasing sales through marketing.